2014
DOI: 10.1177/0268355514537254
|View full text |Cite
|
Sign up to set email alerts
|

Management, clinical outcomes, and complications of acute cannula-related peripheral vein phlebitis of the upper extremity: A retrospective study

Abstract: The cubital fossa region is vulnerable to severe phlebitis and is not recommended as the first site of choice for cannulation. Phlebitis of Baxter scale grade 4 or 5 should be considered for early surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For example, catheter size and insertion site are important factors for catheter longevity. Although the use of larger diameter catheters significantly increases catheter longevity [59] and reduces the risk of accidental removals [15], larger sizes also predict the incidence of phlebitis and subsequent catheter failure [15,60]. Facing the contradictory results on several studies about catheter size, we defined the use of 18 or 20 gauge catheters, which were the most used in the Orthopaedic departments that will participate in the clinical study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, catheter size and insertion site are important factors for catheter longevity. Although the use of larger diameter catheters significantly increases catheter longevity [59] and reduces the risk of accidental removals [15], larger sizes also predict the incidence of phlebitis and subsequent catheter failure [15,60]. Facing the contradictory results on several studies about catheter size, we defined the use of 18 or 20 gauge catheters, which were the most used in the Orthopaedic departments that will participate in the clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have shown that catheter placement in the forearm significantly increased their longevity [15,16,37,43,59]. Catheters in the cubital fossa region have been associated with higher incidence of complications such as phlebitis or occlusion [15,16,37,60].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Cicolini et al observed fewer cases of phlebitis after PVC insertion into the cubital fossa compared to veins of the hand or forearm (12), Dunda et al reported the opposite result and observed even particularly severe courses of phlebitis when it originated from PVCs in the cubital fossa (13).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, no significant associations were found between phlebitis and catheter-related variables. Independent analyses appoint significant relations for the development of phlebitis, including: lower limb puncture (p=0.015) and use of antimicrobials (p=0.009); (12) puncture site in cubital fossa was vulnerable to more severe phlebitis when compared to the forearm (p<0.05); (20) regions of flexion or great mo- bility contribute to traumatic phlebitis; (12) closed infusion systems reduce phlebitis rates by 29% (p=0.004); (4) age (between 60-100 years), smoking (p=0,030), hospitalization at clinical, geriatrics and cardiology wards, emergency admission, use of intravenous antimicrobial drugs, catheter inserted in the back of the hand, calibers 22 and 24 gauge and other catheter materials different from polyurethane; (13) diabetes (p=0.003), 18 gauge caliber (p=0.031), punctured in antecubital fossa region (p=0.001), dwelling time longer than 49 hours (p=0.0000), continuous infusion (p=0.039), use of antimicrobials (p=0.002); (21) hospitalization time longer than 18 days (p=0.002) and dwelling time longer than 72 hours (p=<0.001). (10) A study that related the catheter dwelling time with phlebitis identified its development in 28% of the catheters between fourth and fifth day of the dwelling time (p=0.03).…”
Section: Discussionmentioning
confidence: 99%